An In-depth Analysis of Quiet-Sun IRIS Brightenings - Llŷr Dafydd Humphries; Huw Morgan; David Kuridze (The Astrophysical Journal)
Small-scale brightenings are ubiquitous, dynamic, and energetic phenomena found in the chromosphere. An advanced filter-detection algorithm applied to high-resolution observations from the Interface Region Imaging Spectrograph enables the detection of these brightenings close to the noise level. This algorithm also tracks the movement of these brightenings and extracts their characteristics. This work outlines the results of an in-depth analysis of a quiet-Sun data set including a comparison of a brighter domain—associated with a supergranular boundary—to the quiescent internetwork domains. Several characteristics of brightenings from both domains are extracted and analysed, providing a range of sizes, durations, brightness values, travel distances, and speeds. The “active” quiet-Sun events tend to travel shorter distances and at slower speeds across the plane of the sky than their “true” quiet-Sun counterparts. These results are consistent with the magnetic field model of supergranular photospheric structures and the magnetic canopy model of the chromosphere above. Spectroscopic analyses reveal that bright points demonstrate blueshift (as well as some bidirectionality) and that they may rise from the chromosphere into the transition region. We believe that these bright points are magnetic in nature, are likely the result of magnetic reconnection, and follow current sheets between magnetic field gradients, rather than travel along magnetic field lines themselves.